Surface modification of TiO2 nanotube arrays with metal copper particle for high efficient photocatalytic reduction of Cr(VI). Issue 23 (14th May 2016) - Wu, Mengyao; Duan, Tigang; Chen, Ye; Wen, Qing; Wang, Yuyang; Xin, Hongmei
Abstract: Highly ordered TiO2 nanotube arrays (NTs) have been widely used for photocatalysis application. In this study, to further improve the photocatalysis activity of TiO2 NTs, Cu/TiO2 NTs were prepared through an anodic oxidation and impregnation–reduction method. The morphology and crystalline phase of the pure TiO2 NTs and Cu/TiO2 NTs were characterized by SEM and X-ray diffraction. The photocatalytic performance of Cu/TiO2 NTs was evaluated by photocatalytic reduction of Cr(VI) under UV light. The rate constant of photocatalytic reduction of Cr(VI) on Cu0.01 /TiO2 NTs which had the optimal Cu loading content was 9.5 times higher than that on unmodified TiO2 NTs. And the experiment results of different initial concentration of Cr(VI) and pH demonstrated that they greatly influenced the removal efficiency of Cr(VI). The photoelectric properties of TiO2 NTs with Cu particle loading were investigated by photoelectrochemical characterization, including photocurrent response, open-circuit voltage, electro-chemical impedance spectroscopy Nynquist plots, and Mott–Schottky plots. The enhancement of the photocatalytic performance of Cu/TiO2 NTs indicated that the electrons could transfer faster and be utilized more easily due to the formation of Schottky barrier on the interface of Cu and TiO2 . The detailed electrons transfer mechanism of Cu/TiO2 NTs was proposed.